Avaliação dos impactos das mudanças climáticas sobre a qualidade da água de reservatórios do semiárido Brasileiro. - Raulino, João Batista de Sousa (2021)
The quality of water in lakes and reservoirs has been identified as potentially vulnerable to climate change. This study aims to investigate the impacts of climate change on water quality in reservoirs in the Brazilian semiarid region. An integrated approach of climatic, hydrological and water quality models was used. Part of the simulations revealed a significant impact of decreasing the affluent flow and, consequently, of the stored volume. The reservoirs taken with case studies (Castanho and Orós) responded to the reductions in the affluent flow and stored volume with a significant increase in the internal concentration of PT, with the end of the 21st century experiencing a greater risk of eutrophication. The results also pointed to the influence of seasonality on water quality, with the highest concentrations of PT being recorded during the dry period (June-January). These results suggest that reservoirs in the Northeast of Brazil (NEB) are more vulnerable to the effects of climate change than other regions of the world, as they already experience periodic drought events and gradual reductions in the stocked volume. In addition, the strategies for reducing the affluent load of PT and withdrawn from water have proved to be essential to minimize the impact of climate change on water quality. It is concluded that the sustainable management of water resources in semi-arid basins requires the assessment of the impacts of climate change in both the quantity and quality of water, incorporating the seasonality effect on the internal concentration of pollutants and information on the risk of eutrophication in the reservoirs.